2021
DOI: 10.1111/bph.15621
|View full text |Cite
|
Sign up to set email alerts
|

Lung pharmacokinetics of inhaled and systemic drugs: A clinical evaluation

Abstract: United Kingdom) for scientific exchange and technical advice. We thank the clinical study volunteers for their participation and the site staff for their diligent study conduct. We also thank Richard Claes, PhD, of PharmaGenesis London (London, United Kingdom) for providing medical writing support, which was funded by AstraZeneca (Gothenburg, Sweden) in accordance with Good Publication Practice 3 (GPP3) guidelines (http://www.ismpp.org/gpp3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Thus, it was quite difficult to justify a suitable daily dose [ 24 , [27] , [28] , [29] ]. In a recent phase 1 clinical study of CBD dry powder inhaler, the authors reported a C max of 18.78 ng/mL of CBD [ 30 ], and in general the lung drug concentration should be about 100-fold higher than the concentration in the plasma [ 31 ]. Also, it is worth noting that the extravascular lung fluid according to various reports is about 2–10 mL [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it was quite difficult to justify a suitable daily dose [ 24 , [27] , [28] , [29] ]. In a recent phase 1 clinical study of CBD dry powder inhaler, the authors reported a C max of 18.78 ng/mL of CBD [ 30 ], and in general the lung drug concentration should be about 100-fold higher than the concentration in the plasma [ 31 ]. Also, it is worth noting that the extravascular lung fluid according to various reports is about 2–10 mL [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…For diseases affecting the lungs, such as cystic fibrosis (CF), local delivery of therapeutics is promising since it results in fewer systemic side effects, requires a lower dose compared to systemic delivery, and therapeutics can be administered in multiple ways that are amenable to outpatient use (e.g., nebulizer, dry powder, metered-dose inhaler). (3, 2023) For example, when comparing inhalation versus oral delivery of the same drug substance, lung: plasma drug concentration ratios can reach over 100 (compared to 1.6 for oral administration), making local delivery advantageous for targeting the lung tissues. (23) For CF, this pharmacokinetic profile is attractive for the delivery of gene therapies like CFTR gene replacement or correcting specific CFTR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…(3, 2023) For example, when comparing inhalation versus oral delivery of the same drug substance, lung: plasma drug concentration ratios can reach over 100 (compared to 1.6 for oral administration), making local delivery advantageous for targeting the lung tissues. (23) For CF, this pharmacokinetic profile is attractive for the delivery of gene therapies like CFTR gene replacement or correcting specific CFTR mutations. However, both mucus and cell barriers hinder transport and delivery of therapeutics into the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of this small-size pilot study were promising, we had two main limitations; i.e., only one tobramycin inhaled formulation was available, and we used an analytical method with low sensitivity and selectivity, which resulted in wide variations of EBC concentration profiles of six healthy volunteers ( 12 ). In another interesting work, Sadiq et al ( 13 ) investigated the lung pharmacokinetics of several inhaled and orally administered drugs including salbutamol. They measured the levels of salbutamol in plasma, epithelial lung lining fluid (ELLF), bronchoalveolar lavage (BAL) and in some cases in the filters adsorbing the exhaled particles.…”
Section: Introductionmentioning
confidence: 99%